YOUTH AND ADDICTION TO INFORMATION AND COMMUNICATIONS TECHNOLOGY: INTERNET, SOCIAL NETWORKS AND MOBILE PHONES - Silajdžić, Lamija; Dudić, Anida (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2020)
Addiction, dysfunctional use of „new technologies“ and difficulties in limiting time spent using it, are not unusual due to the increasing usage of the internet. Young people, who are almost constantly connected, are particularly vulnerable. Recognizing the risk of pathological addiction, this paper explores the use of Internet, social networks and mobile phones among young people (N=310) in Bosnia and Herzegovina. The aim of the research is to examine the extent to which young people use the internet, social networks and mobile phones, and what consequences this has on the emotional, cognitive and social functioning of youth. The study was conducted using the most commonly used diagnostic tool for measuring internet addiction, the so-called Internet Addiction Test, and a survey questionnaire created for this research. Results of the study showed a mild level of "new addiction" in youth, which included emotional and cognitive preoccupation with "new“ ICT, neglect of work, lack of self-control and social problems caused by preoccupation with the Internet, social networks and mobile phones.
Keywords: internet, social networks, mobile phone, addiction, young